Adsorption removal of Methylene Blue (MB) dye from aqueous solution by bio-char prepared from Eucalyptus sheathiana bark: kinetic, equilibrium, mechanism, thermodynamic and process design - Dawood, S.; Sen, Tushar; Phan, Chi (Taylor & Francis Ltd., 2016)
Eucalyptus bark (EB) materials-based bio-char adsorbent was synthesised and characterised using SEM-EDS, BET and CHN analyser. The adsorbent surface functional groups were determined by FT-IR analyser. Various textural characteristics such as BET surface area, pore size, bulk density, point of zero charge were also determined. The adsorption potential of these bio-char for the removal of cationic dye Methylene Blue (MB) from aqueous solution was studied. The effects of various temperature profiles on the production of EB bio-char were studied and the most efficient temperature profile was identified at 500°C. Batch adsorption kinetic study showed that the amount of dye adsorbed qt (mg/g) depends on various physicochemical process parameters such as initial solution pH, dye concentration, temperature, adsorbent dose, salt concentration and presence of SDS surfactant. It was found that the extent of MB dye adsorption by EB bio-char increased with the increase of initial dye concentration, contact time, temperature, SDS surfactant concentration and solution pH, but decreased with the increase of adsorbent dose and salt concentration.The optimum adsorption conditions were found at the initial dye concentration of 100 mg/L, initial solution pH of 11.3, adsorbent dose of 10 mg and solution temperature of 55°C. Furthermore, pseudo-first-order, pseudo-second-order and intra-particle diffusion models were fitted to examine the adsorption kinetics and mechanism of adsorption. Equilibrium data were best represented by Langmuir isotherm model and gives a monolayer effective adsorption capacity of bio-char which is comparative to other adsorbents including commercial activated carbon. Thermodynamic parameters suggested that the adsorption was an endothermic, spontaneous and physical in nature. Furthermore, a single-stage batch adsorber design for the MB dye onto EB bio-char particles were presented based on the Langmuir isotherm model equation. These results indicated EB biomass as good and cheap precursor for the production of an effective and environmental friendly bio-char adsorbent.